Targeting central melanocortin receptors: a promising novel approach for treating alcohol abuse disorders - Olney, Jeffrey J.; Navarro, Montserrat; Thiele, Todd E. (Frontiers in Neuroscience, 2014)
The melanocortin (MC) peptides are produced centrally by propiomelanocortin (POMC) neurons within the arcuate nucleus of the hypothalamus and act through five seven-transmembrane G-protein coupled melanocortin receptor (MCR) subtypes. The MC3R and MC4R subtypes, the most abundant central MCRs, are widely expressed in brain regions known to modulate neurobiological responses to ethanol, including regions of the hypothalamus and extended amygdala. Agouti-related protein (AgRP), also produced in the arcuate nucleus, is secreted in terminals expressing MCRs and functions as an endogenous MCR antagonist. This review highlights recent genetic and pharmacological findings that have implicated roles for the MC and AgRP systems in modulating ethanol consumption. Ethanol consumption is associated with significant alterations in the expression levels of various MC peptides/protein, which suggests that ethanol-induced perturbations of MC/AgRP signaling may modulate excessive ethanol intake. Consistently, MCR agonists decrease, and AgRP increases, ethanol consumption in mice. MCR agonists fail to blunt ethanol intake in mutant mice lacking the MC4R, suggesting that the protective effects of MCR agonists are modulated by the MC4R. Interestingly, recent evidence reveals that MCR agonists are more effective at blunting binge-like ethanol intake in mutant mice lacking the MC3R, suggesting that the MC3R has opposing effects on the MC4R. Finally, mutant mice lacking AgRP exhibit blunted voluntary and binge-like ethanol drinking, consistent with pharmacological studies. Collectively, these preclinical observations provide compelling evidence that compounds that target the MC system may provide therapeutic value for treating alcohol abuse disorders and that the utilization of currently available MC-targeting compounds- such as those being used to treat eating disorders- may be used as effective treatments to this end.